2014
DOI: 10.1002/hup.2405
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine administration in healthy non-smokers reduces appetite but does not alter plasma ghrelin

Abstract: These results do not support a key role of peripheral ghrelin secretion in weight changes related to smoking or smoking cessation, but do not rule out that central nervous system ghrelin is involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Future studies may also be strengthened by linking these hormones with appetite and weight changes among smokers after cessation and over a longer period of time. Although we assessed total ghrelin instead of acetylated, active ghrelin, we note that total ghrelin has been related to craving with acute nicotine dosing (Pilhatsch, Scheuing et al 2014). Finally, additional experimental control over food intake prior to blood sampling should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies may also be strengthened by linking these hormones with appetite and weight changes among smokers after cessation and over a longer period of time. Although we assessed total ghrelin instead of acetylated, active ghrelin, we note that total ghrelin has been related to craving with acute nicotine dosing (Pilhatsch, Scheuing et al 2014). Finally, additional experimental control over food intake prior to blood sampling should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Since the samples were collected to assess stress hormones for a larger project, procedures for collecting and preparing of samples for acetylated active ghrelin were not justified. Furthermore, the literature indicates that total ghrelin data yield useful information (Pilhatsch, Scheuing et al 2014). Cotinine concentrations in saliva were assayed using enzyme immunoassay (EIA; DRG Diagnostics, Marburg, Germany) with inter- and intra-assay variations below 12%.…”
Section: Methodsmentioning
confidence: 99%
“…The results of these are very disparate and the studies differ significantly in methodology. Some studies could not corroborate that smoking or smoking cessation alters ghrelin plasma levels [23,24]. Others found that plasma levels of ghrelin were downregulated in subjects exposed to cigarette smoke [25,26,] which seems to contrast findings showing ghrelin levels to be upregulated by exposure to cigarette smoke [27] and downregulated in abstinent smokers [28].…”
Section: Introductionmentioning
confidence: 68%
“…A few underlying causes have been mentioned, including nicotine use,191 physical discomfort such as dyspnoea and increased breathing effort,192 depression, and anxiety,193 seen in COPD194 as well as in NSCLC 195, 196…”
Section: Compromised Dietary Intakementioning
confidence: 99%
“…172 Anorexia It is acknowledged that apparently normal dietary intake in COPD patients may be insufficient to meet elevated energy requirements, but reduced food intake may also be caused by anorexia, that is, loss of appetite. 190 A few underlying causes have been mentioned, including nicotine use, 191 physical discomfort such as dyspnoea and increased breathing effort, 192 depression, and anxiety, 193 seen in COPD 194 as well as in NSCLC. 195,196 Besides pulmonary and psychological symptoms, COPD patients often experience pain.…”
Section: Compromised Dietary Intakementioning
confidence: 99%